The significance of electricity supply sustainability to industrial growth in South Africa - Benedict B. Ateba; Johannes J. Prinsloo; Remigiusz Gawlik (Energy Reports, 2019)
Objective: The South African business environment is characterized by supply uncertainties, which have large economic implications on the country's capacity to achieve its industrial goals. South Africa's industrial decline and falling economic growth is directly associated with decreasing electricity sustainability, as the industrial sector is the main economic contributor to South Africa's GDP. This study aimed at indicating the nexus of electricity supply and industrial growth in South Africa and to appraise the effects of unsustainable supply on industrial operations. The study also assessed industrial and administrative efforts towards sustainable supply of electricity for industries. Methods: The empirical research utilized a quantitative research design. The study geography was focused in the Gauteng and North West provinces of South Africa. A purposive-convenience sampling was utilized. However, quota-sampling guidelines were considered in targeting actual participants. Enterprises across the service, manufacturing and mining industries were sampled. Descriptive and Bivariate statistics were performed. Findings: Results reflected unsustainable electricity supply for the industrial sector and the poor sustainability has an impact on the industrial growth in South Africa. Results also note that most enterprises is challenge in instituting mitigation strategies such as Small, Micro, Medium Enterprises (SMME's) across industries. The phenomenon tends to impact electricity intensive and non-electricity-intensive industries differently. Conclusions: The public sector should apply the good governance framework to ensure policies that will priorities electricity supply sustainability to industries. Enterprises are also advised to institute mitigation mechanisms.
Keywords: 330; Business performance; Business sustainability; Decision-making; Electricity adequacy; Electricity supply; Industrial growth